2008
DOI: 10.1007/s11999-008-0343-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Differentiation of Synovial Sarcoma and Its Therapeutic Application

Abstract: Synovial sarcoma is a rare sarcoma of unknown histologic origin. We previously reported the gene expression profile of synovial sarcoma was closely related to that of malignant peripheral nerve sheath tumors, and the fibroblast growth factor (FGF) signal was one of the main growth signals in synovial sarcoma. Here we further demonstrate the neural origin of synovial sarcoma using primary tumors and cell lines. The expression of neural tissuerelated genes was confirmed in synovial sarcoma tumor tissues, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
8
27
0
1
Order By: Relevance
“…On the contrary, the present study showed that the expression of some neural tissue-related genes was downregulated upon SS18-SSX silencing at the transcriptional and translational levels, suggesting that SS18-SSX expression itself may be responsible, at least in part, for neuronal phenotype of SS through the regulation of neural tissue-related genes. These experimental data are consistent with the findings of sequential studies that SS was clustered into one group with malignant peripheral nerve sheath tumor and several SS cell lines can undergo neural differentiation upon treatment with various differentiation-inducing agents [40,41]. Moreover, those data may be parallel to the growing evidence that expression of the neural-specific markers of Ewing's sarcoma is a result of upregulation by EWS-FLI1 fusion protein rather than dependent on the cellular origin of Ewing's sarcoma [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, the present study showed that the expression of some neural tissue-related genes was downregulated upon SS18-SSX silencing at the transcriptional and translational levels, suggesting that SS18-SSX expression itself may be responsible, at least in part, for neuronal phenotype of SS through the regulation of neural tissue-related genes. These experimental data are consistent with the findings of sequential studies that SS was clustered into one group with malignant peripheral nerve sheath tumor and several SS cell lines can undergo neural differentiation upon treatment with various differentiation-inducing agents [40,41]. Moreover, those data may be parallel to the growing evidence that expression of the neural-specific markers of Ewing's sarcoma is a result of upregulation by EWS-FLI1 fusion protein rather than dependent on the cellular origin of Ewing's sarcoma [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Many of the above findings have been confirmed at the protein level in patient specimens, including FZD10 (54), HES1 (55), NY-ESO-1 (56), BMPR2 (57), SALL2 and EGFR (58), BCL2 (59), SOX9 (60), FGFs and their receptors (61), PDGFRA (52), and Wnt pathway mediators (discussed further in the next section).…”
Section: Additional Molecular Changes Found In Synovial Sarcoma Tumentioning
confidence: 74%
“…In addition, although the literature contains many in vitro studies showing the neurotrophic function of BMPs [1,3,10,12,15], their distribution and the pattern of expression has not previously been demonstrated in vivo. We therefore determined (1) whether BMP-2, -7 and their receptors (BMPRs) are expressed in the normal sciatic nerves of rats; (2) if so, where they are distributed in the injured nerve; and (3) whether BMPs and BMPRs are expressed in the vessels within the perineurium after the nerve transection.…”
Section: Discussionmentioning
confidence: 99%